Keigo to use and to be used: Reevaluation of keigo learning in Japanese language classes - Yasutaka Maruki (Journal of Japanese Language Education and Linguistics, 2022)
For Japanese language speakers, including native speakers, the formal expression of polite, honorific, and humble forms, called keigo, has been a great challenge to master. This research summarizes the challenges discussed by the previous researchers and will introduce three pedagogical methods of learning and practicing keigo: a conversation with one’s future self, the first encounter conversation, and a spiritual or sacred conversation. Different from methods introduced in previous researches, these methods focus on the use of keigo in one’s true self-expressions rather than reactive or objective expressions.